Investigation of the process of vibro-impact interaction of vibration activator blades with two-phase environment “Hydrate lime – water” - Novitskyi, Yaroslav; Lutsuk, Iryna; Zagraj, Andrij; Borovets, Zenon (Видавництво Львівської політехніки, 2022)
The process of mechanical activation of hydrated lime in the vibratory activator of the bunker type is investigated in the work. Economic and environmental effect in the production of reinforced concrete structures is achieved through the use of highly active hydrated lime as a modifying reinforcing additive to concrete based on Portland cement. Theoretical and experimental studies of the influence of vibration displacement parameters of the mixture on the rate and degree of dispersion of hydrated lime and the efficiency of vibroactivation are determined.
Keywords: highly active hydrated lime; vibroactivated lime; lime-colloidal system; lime dispersion; dynamic viscosity; vibration activator; vibration displacement; vibration activation efficiency